Glutamine potentiates gentamicin to kill lab-evolved gentamicin-resistant and clinically isolated multidrug-resistant Escherichia coli - Chen, Yue-tao; Ma, Yan-mei; Peng, Xuan-xian; Li, Hui (Frontiers in Microbiology, 2022)
Gentamicin is a conventional antibiotic in clinic. With a wide use of the drug, gentamicin-resistant Escherichia coli are an ever-increasing problem that causes infection in both human health and animal feeding. Thus, it is especially important to restore gentamicin-mediated killing efficacy. Here, E. coli K12 BW25113 cells were passaged in medium with and without gentamicin and obtain gentamicin-resistant (K12-RGEN) and control (K12-S) strains, respectively. Using a GC-MS metabolomics approach, K12-RGEN metabolome was characterized as more decreased metabolites than increased metabolites and the depression of all or almost metabolites in most enriched metabolic pathways. Alanine, aspartate and glutamate metabolism and glutamine within the metabolic pathway were identified as the most key metabolic pathway and the most crucial biomarker, respectively. Exogenous glutamine potentiated gentamicin-mediated killing efficacy in glutamine and gentamicin dose- and time-dependent manners in K12-RGEN. Further experiments showed that glutamine-enabled killing by gentamicin was effective to clinically isolated multidrug-resistant E. coli. These results suggest that glutamine provides an ideal metabolic environment to restore gentamicin-mediated killing, which not only indicates that glutamine is a broad-spectrum antibiotic synergist, but also expands the range of metabolites that contribute to the bactericidal efficiency of aminoglycosides.